Analysis of the Dynamic Interference between Stator and Rotor of a Refrigeration Compressor Motor by using Finite Element Method - Mohd Aizat bin Mohd Nordin, Mohd Aizat (Universiti Teknologi Petronas, 2009)
This project is about the study and analysis of a finite element model of a hermetic, single-vane compressor and a single-phase alternating current induction motor assembled in a same housing. Interference during operation between stator and rotor of the compressor motor had caused high scrap rate to the manufacturer of the compressor unit. The stator and housing of the compressor unit is rigid, while the rotor shaft is being pictured as a cantilever beam. The objective of this project is to analyze the dynamic interference between stator and rotor by means of modeling and simulating the physical aspects of this unit and to determine the mechanical response of the system due to force inputs characteristic of those encountered during operating conditions. The displacements due to these forces are being examined and they are being scaled to develop the motor parameters necessary to produce the radial forces required for the stator/rotor interference. Finite element analysis (FEA) method is being adapted during modeling and simulation. The computer program that was used to build up the model is CATIA and the model is simulated using ANSYS. A brief research has been done through internet and books on refrigeration compressor motor have been studied and analyzed, and drawing skills using CATIA has been mastered by the author. Microsoft Excel software also used in order to iterate the formula calculation for different input value.